Early-Life Social Isolation Impairs the Gonadotropin-Inhibitory Hormone Neuronal Activity and Serotonergic System in Male Rats - Soga, Tomoko; Teo, Chuin Hau; Cham, Kai Lin; Idris, Marshita Mohd; Parhar, Ishwar S. (Frontiers in Endocrinology, 2015)
Social isolation in early life deregulates the serotonergic system of the brain, compromising reproductive function. Gonadotropin-inhibitory hormone (GnIH) neurons in the dorsomedial hypothalamic nucleus are critical to the inhibitory regulation of gonadotropin-releasing hormone neuronal activity in the brain and release of luteinising hormone by the pituitary gland. Although GnIH responds to stress, the role of GnIH in social isolation-induced deregulation of the serotonin system and reproductive function remains unclear. We investigated the effect of social isolation in early life on the serotonergic–GnIH neuronal system using enhanced green fluorescent protein (EGFP)-tagged GnIH-transgenic rats. Socially isolated rats were observed for anxious and depressive behaviours. Using immunohistochemistry, we examined c-Fos protein expression in EGFP–GnIH neurons in 9-week-old adult male rats after 6 weeks post-weaning isolation or group -housing. We also inspected serotonergic fibre juxtapositions in EGFP–GnIH neurons in control and socially isolated male rats. Socially isolated rats exhibited anxious and depressive behaviours. The total number of EGFP–GnIH neurons was the same in control and socially isolated rats, but c-Fos expression in GnIH neurons was significantly reduced in socially isolated rats. Serotonin fibre juxtapositions on EGFP–GnIH neurons was also lower in socially isolated rats. In addition, levels of tryptophan hydroxylase mRNA expression in the dorsal raphe nucleus were significantly attenuated in these rats. These results suggest that social isolation in early life results in lower serotonin levels, which reduce GnIH neuronal activity and may lead to reproductive failure.